Development and Implementation of Financial Recording Application at PT Indo Vista Sejahtera Using Agile Framework - Nico Dwi Putra; Yefta Christian (Cakrawala Repositori IMWI, 2023)
Indo Vista Sejahtera is a company that runs on electrical engineer services business, that was built on April 12th, 2006. Their method of financial recording is previously done manually using Microsoft excel which result in lack of efficiency in their work as a running business. The purpose of this project is to help Indo Vista Sejahtera company to improve their financial recording by creating a financial recording software. The data for financial recording software gathered from conducting interview and Observation at Indo Vista Sejahtera company, and the software was created using C# as the programing language, SQL as the database and AGILE as the framework of this project. AGILE is a model consist of 6 process which is requirements which is finding requirement for creating the software, design which is designing the software, development which is creating and developing the software, testing which is testing or debugging the software, deployment which is initialization of the software to their system, and review which is reviewing the software. The result of this project to create a simple bookkeeping software to improve their efficiency in financial recording.